INVESTIGATION OF SCIENCE TEACHERS' ANXIETY ABOUT ARTIFICIAL INTELLIGENCE: A PHENOMENOLOGICAL STUDY - Vildan Yalçın; Hasan Gökçe; Oğuzhan Nacaroğlu (Istraživanja u Pedagogiji)
This study aims to examine science teachers' views and concerns about artificial intelligence (AI). Phenomenology design, one of the qualitative research method designs, was used in the study. The study group consisted of five science teachers, one doctoral and four master's degree graduates. Semi-structured interview was preferred as a data collection tool. Inductive content analysis was used to analyze the data. Participants defined AI as robots with humanoid behavior and alternative learning tools. Teachers stated that AI increased academic achievement, motivation and class participation rate. It was found that the participants' concerns about AI stemmed from lack of experience and knowledge, security issues and reliability of information. It was also concluded that the participants were concerned about workload, asocialization, decrease in skills, and privacy of personal data. The participants stated that they had problems in terms of being technologically inadequate, not being able to adapt to AI and lack of knowledge, inadequate AI outputs, and difficulties in applied trainings. It is recommended that science teachers should be given practical trainings to reduce their concerns about AI.